Low clonogenic potential of circulating angiogenic cells is associated with lower density of capillaries in skeletal muscle in patients with impaired glucose tolerance. Issue 4 (5th May 2013) - Prior, Steven J.; Ryan, Alice S.
Abstract: Background: Reduced density of capillaries in skeletal muscle can limit insulin, glucose, and oxygen supply to the muscle, thereby contributing to worsening metabolism in older adults. The lower skeletal muscle capillarization in impaired glucose tolerance (IGT) may partially be due to circulating angiogenic cell dysfunction. Circulating angiogenic cells maintain the vasculature and promote angiogenesis, but circulating angiogenic cell number and function may be reduced in IGT. The goal of this study was to determine whether the clonogenic potential of circulating angiogenic cells is lower in IGT compared with normal‐glucose‐tolerant (NGT) controls and is associated with skeletal muscle capillarization. Methods: Glucose tolerance, endothelial cell colony‐forming unit (CFU‐EC) number, and vastus lateralis capillary density were measured in sedentary, older (62 ± 1 years, mean ± SEM) men and women with NGT ( n = 16) and IGT ( n = 12). Results: Adults with IGT had 43% lower CFU‐EC number (11.4 ± 2.3 versus 20.1 ± 2.0 colonies, p < 0.01) and 12% lower capillary density (291 ± 11 versus 330 ± 9 capillaries/mm 2, p < 0.01) compared with those with NGT. In regression analyses, CFU‐EC number inversely correlated with 120‐min postprandial glucose in all subjects ( r = −0.47, p < 0.05), and capillary density was directly associated with CFU‐EC number ( r = 0.53, p < 0.05). Conclusions: We conclude that the clonogenic potential of circulating angiogenic cells is lower in sedentary older adults with IGT and is associated with lower skeletal muscle capillarization. Low circulating angiogenic cell clonogenic potential in IGT suggests a state of impaired angiogenesis occurring prior to overt type 2 diabetes that may mediate early microvascular changes in the development and progression of IGT to type 2 diabetes. Published 2013. This article is a U.S. Government work and is in the public domain in the USA.